Catheter Ablation of Premature Ventricular Contractions Originating in the Aortic Sinus Cusp or Great Cardiac Vein: Two QRS Morphologies with One Origin. Issue 9 (20th June 2015) - WANG, YU‐BIN; MA, JUAN; DONG, JIAN‐ZENG; BAI, RONG; WANG, JING; LI, SONG‐NAN; YU, RONG‐HUI; LONG, DE‐YONG; MA, CHANG‐SHENG; CHU, JIAN‐MIN
<x xml:space="preserve">Abstract</x> Background Premature ventricular contractions (PVCs) originating from aortic sinus cusps (ASCs) can exhibit preferential conduction to right ventricular outflow tract (RVOT). Objectives This study aimed to examine the electrophysiological characteristics for guiding catheter ablation in patients with two morphological types of PVCs that originate from ASCs or the great cardiac vein (GCV). Methods We analyzed electrocardiogram from 10 patients with PVCs of two QRS morphologies. The patients who exhibited dominant left bundle branch block (LBBB) QRS morphology and less right bundle branch block (RBBB) morphology were designated as group 1 (n = 7), and those with dominant RBBB QRS morphology were designated as group 2 (n = 3). During PVCs, electroanatomical mapping was performed in both RVOT and ASC in group 1 and only performed in ASC or GCV in group 2. Results In group 1, the earliest ventricular activation preceding the onset of the QRS complex (V‐QRS) was recorded for 27 ± 6 ms (range 18–36 ms) in RVOT and 25 ± 6 ms (range 18–34 ms) in the ASC, while V‐QRS was recorded for 28 ms, 42 ms, 40 ms in the ASC or GCV in group 2. All patients were successfully ablated at one site finally, including left coronary cusp in seven, left‐right coronary cusp commissure in two, and GCV in one. None of the patients experienced recurrence or complications during the 18.4 ± 5.1 (range 6–24 months) months of follow‐up. Conclusions Two QRS morphologies (LBBB and RBBB with inferior axis) in PVCs could be a predictor of PVCs originating from ASC or GCV.